Evaluation of pleural vents vs indwelling chest drains for the management of post CT-guided biopsy pneumothorax by radiologists and respiratory physicians, at Glan Clwyd Hospital, Wales - Sam Doherty; Elen Jones; Rajiyah Hussain; Diab Alsouki; Lawi Suissa; Ahmed Abou-Haggar (Clinical Medicine)
Introduction: Computed tomography (CT)-guided biopsy (CTGB) of the lung is a commonly used procedure for diagnosing lung cancer at Glan Clwyd Hospital. Pneumothorax is a known complication of CTGB with an incidence rate of ∼25%.1 Depending on the size of the pneumothorax, the time of occurrence and the clinician performing the biopsy they are treated in three main ways: (i) observation; (ii) intercostal drain; or (iii) pleural vents. Management with a traditional intercostal chest drain (ICD) often leads to unplanned hospital admissions for observation and management.1 Use of pleural vents is a recent change in practice at Glan Clwyd Hospital. Pleural vents allow full patient mobility and may reduce the need for inpatient management. The primary aim of this study was to compare length of stay in patients who received pleural vents versus ICDs in the management of post-CTGB pneumothorax. Materials and Methods: This was a retrospective analysis of 98 scheduled CTGB, which took place. These biopsies occurred over a 1-year period (2 November 2023 to 19 November 2024) at Glan Clwyd Hospital. Of the 98 scheduled biopsies, 17 were excluded for the following reasons:- Resolution of lesions (1);- Abandonment of biopsy or did not attend (8);- Biopsies taken from anatomical areas outside of the lungs (3);- Patient no longer fit for procedure (1);- Access to biopsy site not possible (1)- Resolution of lesion (3).81 biopsies remained for further analysis. Results and Discussion: Of the 81 patients, 39 experienced complications, 30 of which were pneumothorax and 9 were haemothorax. This was noted to be a pneumothorax complication rate of 37%, higher than the reported average.1 Of those 30 patients who developed a pneumothorax, 9 required intervention. Of these 9 patients, 4 were managed by pleural vents inserted at the time of the CT biopsy by the operating radiologist and 5 had ICDs inserted by the respiratory team. Modal length of stay for those with pleural vents was 1 day compared with 3 days for those with chest drains (Fig 1). Conclusion: From these data, we concluded that the introduction of pleural vents led to a reduced length of stay compared with ICDs for the management of post-CTBG pneumothorax. As a quality improvement measure, we suggested that pleural vents become the first line in the management of CTGB-related pneumothorax at Glan Clwyd Hospital. In the future, we hope to develop an outpatient department pathway whereby patients can leave hospital the same day with pleural vent treatment of their post-CCTBG pneumothorax, eliminating the need for hospital stay.